2016
DOI: 10.1161/circresaha.116.306924
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Considerations of Antihyperglycemic Medications for Type 2 Diabetes

Abstract: Prevalent and incident heart failure (HF) is increased in people with type 2 diabetes mellitus, with riskdirectly associated with the severity of hyperglycemia. Furthermore, in patients with type 2 diabetes mellitus, mortality is increased ≈10-fold in patients with versus without HF. Reducing HF with antihyperglycemic therapies, however, has been unsuccessful until recently. In fact, HF as an important outcome in patients with type 2 diabetes mellitus seems to be heterogeneously modulated by antihyperglycemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 150 publications
0
32
0
3
Order By: Relevance
“…More than one-third of these people will also suffer from diabetes (3,4). A recent study of 1.9 million individuals demonstrated that CHF was second only to peripheral artery disease as a cardiovascular complication of type 2 diabetes (5).…”
Section: Discussionmentioning
confidence: 99%
“…More than one-third of these people will also suffer from diabetes (3,4). A recent study of 1.9 million individuals demonstrated that CHF was second only to peripheral artery disease as a cardiovascular complication of type 2 diabetes (5).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes may also cause cardiac dysfunction in the absence of overt macrovascular disease due to hyperglycaemia-related cardiomyopathy, even in patients in type 1 diabetes [3]. HF is of major interest as it is the one cardiovascular outcome for which the risk has unequivocally been shown to be increased by some glucose-lowering therapies, particularly thiazolidinediones (glitazones) [4,5], whereas metformin appears to be safe [6]. Recently, some concerns have also been raised with the dipeptidyl peptidase (DPP)-4 inhibitor saxagliptin, following the publication of the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR) -Thrombolysis in Myocardial Infarction (TIMI) 53 trial [7], a finding that casts some suspicion on the entire incretin-based pharmacological class [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant presence of both conditions worsens prognosis and complicates treatment. Moreover, data suggest strict glycemic control may not meaningfully change risk of HF in patients with DM and multiple trials of glucose lowering therapies have now been associated with increased or decreased risk of HF events, compared with placebo (13–18). …”
mentioning
confidence: 99%
“…Although recent publications have emphasized the need for improved description of HF events in DM trials, HF data capture within such trials has not been systematically characterized (1820). We present a systematic review of the ascertainment of baseline HF, incident HF, and reporting of HF-related clinical events within published clinical trials of glucose lowering therapies.…”
mentioning
confidence: 99%